2008
DOI: 10.5694/j.1326-5377.2008.tb02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking by professional Australian Football League (AFL) players: prevalence and correlates of risk

Abstract: Objectives: To examine self‐reported patterns of alcohol consumption and experience of alcohol‐related harms among professional Australian Football League (AFL) players. Design, setting and participants: Cross‐sectional survey of player alcohol consumption and self‐reported alcohol‐related harms among members of all 16 professional AFL clubs. Data relating to the 2006 football year were collected between 25 July and 30 August 2006 at regular football training sessions using a self‐administered structured quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 10 publications
6
50
1
Order By: Relevance
“…For the purposes of reporting and analysis, studies were grouped according to the following major mental health constructs: anger and aggression ( N  = 2) [29, 30], anxiety ( N  = 4) [3134], eating disorder and body image ( N  = 10) [21, 3543], general-prevalence studies ( N  = 10) [23, 4452], help seeking ( N  = 1) [11], sleep ( N  = 1) [53], stress and coping ( N  = 22) [6486], substance use ( N  = 9) [54–62] and wellbeing ( N  = 1) [63]. The included studies examined athletes from a broad range of individual sports (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purposes of reporting and analysis, studies were grouped according to the following major mental health constructs: anger and aggression ( N  = 2) [29, 30], anxiety ( N  = 4) [3134], eating disorder and body image ( N  = 10) [21, 3543], general-prevalence studies ( N  = 10) [23, 4452], help seeking ( N  = 1) [11], sleep ( N  = 1) [53], stress and coping ( N  = 22) [6486], substance use ( N  = 9) [54–62] and wellbeing ( N  = 1) [63]. The included studies examined athletes from a broad range of individual sports (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The studies on elite athlete substance use focused on either alcohol [54, 59, 60], or other drugs [5558, 61, 62] (see Table 5). Studies related to alcohol use indicated higher rates of consumption in athletes relative to the general community [59, 60].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the licensee will be required at all times alcohol is sold. The intervention will target the social and cultural environment of the football club by: prohibiting drinking games and promotions including cheap or discounted drinks,28 alcohol-only awards or prizes27 and all-you-can-drink functions; introducing a club-based alcohol policy; and routine patrolling of sporting club grounds to monitor and inform spectators of expectations regarding alcohol use and consumption at the venue. The comprehensive, multicomponent intervention utilises a three-tiered accreditation framework designed to motivate intervention implementation.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Given the prevalence of at-risk consumption among sports players and fans, interventions targeting alcohol consumption at sporting settings may represent an effective strategy in mitigating the adverse effects of excessive alcohol consumption. Such interventions may include the sale of low-alcohol and non-alcohol beverages22 and the prohibition of drinking games and promotions including cheap or discounted drinks23 and alcohol-only awards or prizes 24…”
Section: Introductionmentioning
confidence: 99%